The cycle of insecurity: reassessing the security dilemma as a conflict analysis tool - Mitchell, David (My University, 2019)
This article critically reassesses one of the classic ideas in International Relations, the security dilemma. It argues that the key insight of security dilemma theory has been obscured – by reductionist debates on single causes of conflict, inconclusive applications, and definitional disputes – and that the security dilemma’s enduring utility is as a model of the relational dynamic inherent in all conflict, the cycle of insecurity. Through a reappraisal of the literature, the article elucidates three essential dimensions of the cycle: an environment of structural uncertainty; interdependent collective identities; and an escalating and self-perpetuating dynamic. The power and validity of this threefold framework is then demonstrated by an analysis of the conflict in Northern Ireland, a hitherto unexplored case study in the security dilemma literature. The article shows how this construction of the security dilemma offers a convincing, comprehensive and flexible conflict analysis tool which is of both scholarly and practical utility.
PUBLISHED
Keywords: Security dilemma; Northern Ireland; Insecurity